Allergic alveolitis due to wood-rot fungi - Bryant, D H; Rogers, P (Allergy and asthma proceedings, 1991)
Farmer's lung is rare in Australia whereas allergic alveolitis due to domestic fungal exposure ("domestic allergic alveolitis") is common. However there has been no systematic analysis of the fungi responsible for domestic allergic alveolitis in Australia. The aim of this study was to determine the sources and types of fungi that cause this type of alveolitis in Australia. Twelve subjects with recently diagnosed, biopsy proved, alveolitis thought on clinical grounds to be due to domestic fungal exposure were studied. The houses of all subjects were inspected, and fungal samples were taken. All lived in substandard inner city dwellings. Extensive wood decay was found in 10/12 while 4/12 also had obvious fungal growth on damp walls. Twelve fungal species were identified including Serpula lacrymans (8/12), Paecilomyces variottii (6/12), Aspergillus fumigatus (5/12), and Leucogyrophana pinastri (2/12). No single fungal group predominated. Nine of 12 patients showed positive precipitin results to one or more of the isolated fungi. Inhalation tests were done with extracts of Serpula lacrymans, Geotrichum candidum, and Aspergillus fumigatus in six of the patients and a positive late response to one or more of the fungi was observed in five of these. Relocation of the patients to a new dwelling resulted in improvement in each case.